1998
DOI: 10.1063/1.122765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of well number on organic multiple-quantum-well electroluminescent device characteristics

Abstract: A doping technique for fabricating organic multiple-quantum-well electroluminescent (EL) devices is demonstrated. This device consists of N,N′-Bis(3-methyphenyl)-N,N′-diphenylbenzidine used as a hole transporter, undoped tris(8-quinolinolato) aluminum (Alq) as a barrier potential or electron transporter, and Alq doped with 5,6,11,12-tetraphenylnaphthacene as a potential well and an emitter. Our experimental results suggest that the double-quantum-well EL devices show the optimum emission characteristics. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…In our previous work, a sort of quantum well structure EL device with significant quantum size effect has been fabricated by the doping method. [18][19][20] We also studied the effects of well thickness and well number on the EL device characteristics, 18 the results show that the EL device with the well thickness of 3 nm and the well number of 2 exhibits the optimum performance in our experimental condition. In order to further improve the device efficiency and brightness, we have designed and fabricated a new kind of double-quantum-well ͑DQW͒ device using the doping method.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In our previous work, a sort of quantum well structure EL device with significant quantum size effect has been fabricated by the doping method. [18][19][20] We also studied the effects of well thickness and well number on the EL device characteristics, 18 the results show that the EL device with the well thickness of 3 nm and the well number of 2 exhibits the optimum performance in our experimental condition. In order to further improve the device efficiency and brightness, we have designed and fabricated a new kind of double-quantum-well ͑DQW͒ device using the doping method.…”
mentioning
confidence: 91%
“…Additionally, we have investigated the effect of well number on the characteristics of organic quantum well structure device and found that the excessive well number will cause the inferior luminance properties. 18 It suggested that there are some negative effects of the interfaces, such as defects or nonradiative center and these increases with the increasing of the well number. However, by choosing a suitable well number and designing a suitable structure, the quantum well structure device should possess better luminance properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of well number on the performance of organic EL device has been invested previously. It was found that the excessive well number will cause inferior luminous properties probably due to the negative effects of interface (Huang et al 1998), such as defeats of non-radiative center, which will increase with increasing well number. Moreover, excessive well numbers may also lead to non-uniform distribution of the two types of charge carriers in the well.…”
Section: Improving Current Efficiency Of Organic Light-emitting Devicementioning
confidence: 98%
“…The easy of fabrication, robustness high efficiency and small weight and thickness are major advantages over competing technologies such as liquid crystals (Tang and Van Slyke 1897; Kido et al 1995;Cao et al 1996;Shen et al 1997;Huang and Mason 2001). In its simplest case, an OLED consists of hole transporting layer (HTL), emitting layer (EML), electron transporting layer (ETL) sandwiched between two metal electrodes, one with high (anode) and one with low (cathode) work function.…”
Section: Introductionmentioning
confidence: 98%